Peran Kepala Desa dalam Menanggulangi Banjir di Desa Monas Kecamatan Monano Kabupaten Gorontalo Utara - Adelia Adelia Hasu; Lisda Van Gobel; Yahya Antu (Publikasi Indonesia, 2023)
This study aims to determine the Role of Village Heads in Overcoming Floods in Monas Village, Monano District, North Gorontalo Regency. This research consists of three focuses, namely Coordinator, Motivator and supervision. The research method used is descriptive qualitative. The results of the study concluded that the coordinator carried out with the Regional Disaster Management Agency (BPBD), BPD, and the head of the hamlet about flood management in Monas Village was not optimal, so that in the event of a flood, BPBD was considered slow in preparing emergency response places or posts, setting up public kitchens, providing basic needs for the community. The village government also lacks monitoring of the condition of the area and environment in Monas village. Lack of dredging and installation of fugitives in flood-affected areas. The motivator carried out by the Village Head in flood management in Monas Village has not been optimal. This can be seen from the lack of participation between the village government and the community in tackling floods, supervision in tackling floods in Monas Village has not been optimal. This can be seen from the attitude or habit of the community who always throw garbage in the river area, the participation of people in flood-affected areas is still very low, the village government rarely checks environmental conditions such as river conditions, waterways and others so that the community also lacks the encouragement to maintain or maintain the cleanliness of the environment.